2010
DOI: 10.1111/j.1365-2133.2010.09708.x
|View full text |Cite
|
Sign up to set email alerts
|

The association between null mutations in the filaggrin gene and contact sensitization to nickel and other chemicals in the general population

Abstract: This study suggests that FLG null mutations may be a risk factor for the development of nickel sensitization. However, ear piercing was a much stronger risk factor in our general population and we could therefore identify a positive association only in women without ear piercings. Contact sensitization to specific chemicals is related to treatment exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 25 publications
10
117
5
Order By: Relevance
“…More recent studies have confirmed the association and identified additional mutations in the FLG gene that predispose to AD in European and Asian populations (64-67). FLG mutations have also been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy, and food allergy (68)(69)(70)(71)(72)(73), suggesting that FLG mutation-associated SC barrier defects lead to increased numbers of episodes of percutaneous allergen exposure (Figure 2). Interestingly, FLG mutations are not associated with asthma without eczema (70,71), and most of the identified asthma-associated genes are not associated with AD (74,75), suggesting that atopic asthma is a distinguishable sub-entity.…”
Section: Major Players In Sc Barrier Dysfunctionmentioning
confidence: 99%
“…More recent studies have confirmed the association and identified additional mutations in the FLG gene that predispose to AD in European and Asian populations (64-67). FLG mutations have also been reported to be associated with atopic asthma, allergic rhinitis, nickel allergy, and food allergy (68)(69)(70)(71)(72)(73), suggesting that FLG mutation-associated SC barrier defects lead to increased numbers of episodes of percutaneous allergen exposure (Figure 2). Interestingly, FLG mutations are not associated with asthma without eczema (70,71), and most of the identified asthma-associated genes are not associated with AD (74,75), suggesting that atopic asthma is a distinguishable sub-entity.…”
Section: Major Players In Sc Barrier Dysfunctionmentioning
confidence: 99%
“…Notably, individuals with a history of atopic dermatitis (AD) appear to be more susceptible to developing nickel allergy; this is not surprising, considering that filaggrin null mutations have been shown to be positively associated with nickel sensitization. 8,9 This fact advances the importance of contact allergy testing in children with recalcitrant or widespread severe AD, because such situations may indicate the presence of underlying or superimposed ACD. 10 Additionally, recognizing the risks of Ni-ACD associated with piercing may justify preemptive avoidance of nickel among patients with AD, to decrease sensitization and morbidity.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately 9% of people of European origin are carrying these variants [ 18,27 ] . More than 40 loss-of-function mutations within the fi laggrin gene have now been reported [ 30 ] .…”
Section: Filaggrin: the Multifunctional Proteinmentioning
confidence: 99%